2023
DOI: 10.1002/jsfa.12952
|View full text |Cite
|
Sign up to set email alerts
|

Pumpkin seed oil: a comprehensive review of extraction methods, nutritional constituents, and health benefits

Zicong Hu,
Chaofan Hu,
Yanpo Li
et al.

Abstract: Pumpkin seed oil (PSO), a rich source of nutrient contents, is extracted from the seeds of different pumpkin varieties for food and medicine industries. Accordingly, this article was designed to provide an evidence‐based review of the literature, with the purpose of achieving practical conclusions involved the extraction technologies, nutritional properties, and validated biological activities of PSO. From the previous literatures, PSOs contain a large proportion of unsaturated fatty acids, with linoleic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…There are various methods for extracting oil from cucurbit seeds: cold-pressed extraction [86,93,112], solvent extraction [86], supercritical fluid extraction, enzyme-assisted aqueous extraction, and ultrasound-assisted extraction [113].…”
Section: Methods Of Cucurbit Oil Extraction For Biodiesel Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are various methods for extracting oil from cucurbit seeds: cold-pressed extraction [86,93,112], solvent extraction [86], supercritical fluid extraction, enzyme-assisted aqueous extraction, and ultrasound-assisted extraction [113].…”
Section: Methods Of Cucurbit Oil Extraction For Biodiesel Productionmentioning
confidence: 99%
“…Before oil extraction, the seeds need to be separated from the pulpy part of the fruit, cleaned, and washed. Then, the seeds are dried, either naturally or in a vacuum oven, at a temperature of 60-75 • C until the moisture content reaches 2% [93,113].…”
Section: Methods Of Cucurbit Oil Extraction For Biodiesel Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pumpkin (Cucurbita maxima), belonging to the Cucurbitaceae family, is one of the important crops in the world. 1 Pumpkin seeds are used as valuable ingredients in the baking industry and are also utilised to produce pumpkin seed oil due to their high oil content (39.7-48.6% w/w). 2,3 Pumpkin seed oil is rich in unsaturated fatty acids (over 80%) and contains many bioactive compounds, such as tocopherols, squalene and phytosterols; [4][5][6][7] in addition, many studies have demonstrated its health bene-ts, such as anti-inammatory, diuretic properties, and preventing atherosclerosis as well as prostate disease.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In recent years, pumpkin seed oil requirement and consumption have been increasing and its application has been studied and demonstrated as a promising functional oil source in food, cosmetics, and pharmaceuticals. 1,7 This drives oil industries to upgrade pumpkin seed oil quality to meet the customer demand and potentially growing market needs.…”
Section: Introductionmentioning
confidence: 99%